SEM-EDAX ANALYSIS OF TAMRA BHASMA PREPARED USING DAMARU YANTRA (AYUSHDHARA, 2018)
Tamra Bhasma (incinerated copper) is one of the most commonly used medicine in the field of Ayurveda as it is indicated for various diseases and proves to be efficacious due to its high potency. Though efficacious if it is not prepared properly it can lead to adverse toxic reactions. There are several references mentioned for the preparation of Tamra Bhasma in the classics. In this study, Copper sheet was taken for the preparation of Bhasma and procedures like Shodhana, Marana using Damaru Yantra followed by successive Puta and Amrutikarana was done as per the classical reference.  During the process of Marana care has to be taken while doing Hingulalepa over the Tamrapatra and continuous monitoring of the process of Urdwapatana has to be done. Analysis of Tamra churna and Bhasma (6th & 28th) using SEM- EDAX stated that Tamra churna after 6 successive Putas showed the presence of Carbon, Oxygen, Sulphur, Copper  and the particle size couldn’t be analysed. Tamra Bhasma on the other hand showed the presence of Oxygen in higher percentage and the percentage of Copper reduced, the particle size could easily be analysed ranging in nanometer scale of 142.4 to 166.2nm thereby proving it to be in the state of a nanoparticle fulfilling the criteria of being a Bhasma.